The effect of weeding time on raspberry (Rubus idaeus L.) crops yield and weed community in Rio Negro Province, Argentina - Scursoni, Julio Alejandro; Cortada, A.; Rezzano, Carlos; Martinez, E.; Vercelli, Federico; Ancalao, Marcos; Cobelo, Claudia Mónica (Elsevier, 2018)
Raspberry (Rubus idaeus L.) is the most important crop in the (Andean Shire), an area situated at the south of Rio Negro Province in the south of Argentina. Organic berries production in this area increased significantly in the last ten years. Weed management in raspberry organic crops is performed by tillage. Excessive tillage can reduce weed species diversity and increase both soil erosion and production costs. Field experiments were carried out with summer and fall fruiting raspberry varieties within the periods 2005–06 and 2006–07 with the aim of studying the effect of different weeding times on (i) raspberry yield, (ii) fruit quality and (iii) weed community richness and abundance. The fruit harvest was carried out two or three times a week during all harvest period for each variety. In addition, fruit quality was assessed at different harvest times. From spring to the end of harvest weed cover and weed species richness were measured for each treatment. The results showed that the most frequent weed removal did not exceed the yield obtained with three weeding operations carried out during spring and summer. This meant an important reduction in cost production, with the advantage of maintaining weed diversity. The presence of weeds did not affect fruit quality. Summer fruiting variety was more competitive than fall fruiting variety.